Development of the Placenta and Brain Are Affected by Selective Serotonin Reuptake Inhibitor Exposure During Critical Periods - Eugenin-Leon, J; Bravo-Flores, K (Springer, 2023)
Selective serotonin reuptake inhibitors (SSRIs) are usually prescribed to treat major depression and anxiety disorders. Fetal brain development exhibits dependency on serotonin (5-hydroxytryptamine, 5-HT) from maternal, placental, and fetal brain sources. At very early fetal stages, fetal serotonin is provided by maternal and placental sources. However, in later fetal stages, brain sources are indispensable for the appropriate development of neural circuitry and the rise of emergent functions implied in behavior acquisition. Thus, susceptible serotonin-related critical periods are recognized, involving the early maternal and placental 5-HT synthesis and the later endogenous 5-HT synthesis in the fetal brain. Acute and chronic exposure to SSRIs during these critical periods may result in short- and long-term placental and brain dysfunctions affecting intrauterine and postnatal life. Maternal and fetal cells express serotonin receptors which make them susceptible to changes in serotonin levels influenced by SSRIs. SSRIs block the serotonin transporter (SERT), which is required for 5-HT reuptake from the synaptic cleft into the presynaptic neuron. Chronic SSRI administration leads to pre- and postsynaptic 5-HT receptor rearrangement. In this review, we focus on the effects of SSRIs administered during critical periods upon placentation and brain development to be considered in evaluating the risk-safety balance in the clinical use of SSRIs. © 2023, Springer Nature Switzerland AG.